2021
DOI: 10.1038/s41598-021-87679-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatitis D virus infection in development of hepatocellular carcinoma among chronic hepatitis B patients treated with nucleotide/nucleoside analogues

Abstract: Hepatitis D virus (HDV) infection increases the risk of hepatocellular carcinoma (HCC) in the natural course of chronic hepatitis B (CHB) patients. Its role in patients treated with nucleotide/nucleoside analogues (NAs) is unclear. We aimed to study the role of hepatitis D in the development of HCC in CHB patients treated with NAs. Altogether, 1349 CHB patients treated with NAs were tested for anti-HDV antibody and RNA. The incidence and risk factors of HCC development were analyzed. Rates of anti-HDV and HDV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
(9 reference statements)
1
18
0
Order By: Relevance
“… 36 A study of Taiwanese chronic hepatitis B patients treated with NA showed that HDV viraemia contributed significantly to the development of HCC, with a 5-year cumulative incidence of 22.2% compared with HDV RNA-negative patients (7.3%, p = 0.01). 37 In the present study, upon stratification by RNA positivity, cirrhosis, elevated ALT, AST, and TE indicating greater than stage 2 fibrosis, were significantly associated with HDV viraemia. The significant association between HDV viraemia and increased ALT levels has also been described in both univariate and multivariate analyses in a cross-sectional study of over 1,500 patients from 15 countries.…”
Section: Discussionsupporting
confidence: 43%
“… 36 A study of Taiwanese chronic hepatitis B patients treated with NA showed that HDV viraemia contributed significantly to the development of HCC, with a 5-year cumulative incidence of 22.2% compared with HDV RNA-negative patients (7.3%, p = 0.01). 37 In the present study, upon stratification by RNA positivity, cirrhosis, elevated ALT, AST, and TE indicating greater than stage 2 fibrosis, were significantly associated with HDV viraemia. The significant association between HDV viraemia and increased ALT levels has also been described in both univariate and multivariate analyses in a cross-sectional study of over 1,500 patients from 15 countries.…”
Section: Discussionsupporting
confidence: 43%
“…Regarding risk factors, cirrhosis, HDV-RNA positivity, age > 50 years old, male gender, and BMI are independently predictive of HCC development in patients with CHB treated with NAs. Interestingly, in the subgroup of those with cirrhosis, HDV-RNA positivity remains independently predictive of HCC [ 88 ].…”
Section: Surveillance In Patients At Riskmentioning
confidence: 99%
“…Previous studies on hepatotropic viruses including HBV, HCV and HDV have frequently shown the significance of viral infection in HCC development [ 6 , 34 , 35 ]. Whether HEV has a similar function in hepatocarcinogenesis remains controversial, but several epidemiological and clinical studies imply a potential role of HEV in the HCC pathogenesis.…”
Section: Clinical Evidence and Epidemiological Studiesmentioning
confidence: 99%
“…Indeed, 78% of all HCC cases are attributable to HBV (53%) or HCV (25%) infection alone [ 4 ]. Current research also suggests hepatitis D virus (HDV) plays a crucial role in HCC formation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%